Group versus Traditional Prenatal Care in Low Risk Women Delivering at Term: a Retrospective Cohort Study - Carter, Ebony B. (J Perinatol, 2017)
BACKGROUND: Group prenatal care (GC) models are receiving increasing attention as a means of preventing preterm birth; yet, there is limited data on whether group care improves perinatal outcomes in in women who deliver at term. OBJECTIVE: The purpose of this study was to evaluate our institutional experience with GC over the last decade and test the hypothesis that GC, compared to traditional individual care (TC), improves perinatal outcomes in women who deliver at term. STUDY DESIGN: We performed a retrospective cohort study of women delivering at term who participated in GC compared to TC. A group of 207 GC patients who delivered at term from 2004–2014 were matched in a 1:2 ratio to 414 patients with term singleton pregnancies who delivered at our institution during the same period by delivery year, maternal age, race, and insurance status. The primary outcome was low birthweight < 2500g. Secondary outcomes included early term birth (37.0–38 6/7 weeks), 5 minute APGAR score <7, special care nursery admission, neonatal intensive care unit (NICU) admission, neonatal demise, cesarean section, and number of prenatal visits. Outcomes were compared between the two groups using univariable statistics. RESULTS: Baseline characteristics were similar between the two matched groups. GC was associated with a significant reduction in low birthweight infants compared to TC (11.1% vs. 19.6%; RR 0.57; 95% confidence interval [CI] 0.37–0.87). Patients in GC were significantly less likely than controls to require cesarean delivery, have low 5 min APGAR scores and need higher level neonatal care (NICU: 1.5% vs. 6.5%; RR 0.22; 95% CI 0.07–0.72). There were no significant differences in rates of early term birth and neonatal demise. CONCLUSION: Low-risk women participating in GC and delivering at term had a lower risk of low birthweight and other adverse perinatal outcomes compared to women in TC. This suggests GC is a promising alternative to individual prenatal care to improve perinatal outcomes in addition to preterm birth.